PENGEMBANGAN USAHA TRADISIONAL UMKM TABARO DANGE KHAS PALU - Steven Ladjepe; Nafadillah Nafadillah; Juniva Juniva; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The Fisherman's Village Tourism is a popular destination for local residents in Palu City. This tourist spot is home to many micro, small, and medium enterprises (MSMEs). One such MSME is Tabaro Dange, a traditional Palu dish. This research employed qualitative methods, employing in-depth interviews and literature review. The potential for Tabaro Dange MSMEs is significant in creating employment opportunities for the community, particularly in Palu City. Challenges faced by entrepreneurs include adverse weather conditions and competition from modern food chains.